Effects of expertise on muscle activity during the hang power clean and hang power snatch compared to snatch and clean pulls - An explorative analysis - Geisler, S.; Havers, T.; Isenmann, E.; Schulze, J.; Lourens, L. K.; Nowak, J.; Held, S.; Haff, G. G. (Journal of Sports Science & Medicine, 2023)
The purpose was to compare the electromyographic (EMG) activity of the Hang Power Clean (HPC) and Hang Power Snatch (HPS) with the Hang Clean Pull (HCP) and Hang Snatch Pull (HSP). Additionally, the influence of weightlifting expertise (beginner, advanced and elite) on EMG activity was analyzed. Twenty-seven weightlifters (beginner: n = 11, age: 23.9 ± 3.2 years, bodyweight: 75.7 ± 10.5 kg; advanced: n = 10, age: 24.8 ± 4.5 years, bodyweight: 69.4 ± 13.9 kg; elite: n = 6, age: 25.5 ± 5.2 years, bodyweight: 75.5 ± 12.5 kg) participated in this study. Participants performed two repetitions of HPC, HPS, HCP, and HSP at 50%, 70%, and 90% 1RM, respectively. The EMG activity of vastus lateralis (VL), gluteus maximus (GM), erector spinae (ES), rectus abdominis (RA) and trapezius (TZ) was recorded and normalized to the maximum voluntary isometric contraction (MVIC) of each muscle. There were significant differences in RA and ES EMG activity at 70% and 90% 1RM during HPC compared to HCP in the beginner group (p < 0.05, Hedges g = 0.50-1.06). Significant greater ES activity was observed in the beginner, advanced, and elite groups (p < 0.05, g = 0.27-0.98) during the HPS when compared to the HSP at 50-90% 1RM. TZ muscle activity was significantly greater at 50% and 70% 1RM in the HCP compared to the HPC in the elite group (p < 0.05, g = 0.61-1.08), while the beginner group reached significance only at 50% 1RM favoring HPC (p < 0.05, g = 0.38). Moreover, the EMG activity of the TZ during the HSP and HPS was significantly different only at 50% 1RM in the elite group and favored HSP (p < 0.05, g = 0.27). No differences were observed between the levels of weightlifting expertise. Based upon the results of this study, the overall pattern of EMG activity of the predominant muscles involved in HPC/HPS and the corresponding weightlifting pulling derivatives, apart from the stabilizing muscle (RA and ES), is similar at higher intensities (>70% 1RM) and expertise does not influence muscle activity.